Investigation of Polycyclic Aromatic Hydrocarbons in Foods - Hampikyan, Hamparsun; Colak, Hilal (Asian Journal of Chemistry, 2010)
Polycyclic aromatic hydrocarbons (PAHs) also known as polycyclic organic matter or polynuclear aromatic hydrocarbons are a class of carcinogenic chemical compounds originating from incomplete combustion of organic matter and geochemical processes. Exposure to PAHs is a major concern for human health. Breathing the air near coal-tar, asphalt production or applications, cigarette smoke, wood smoke, vehicle exhausts, fumes from chimneys, inhalation of polluted air, eating grilled or charred meats, any food with PAHs deposited on them during growing or processing, with drinking water and coal-tar-containing medications are the main sources of PAH exposure. Under the guidance of the latest literatures, the emphasis in this review will be placed on the general information about PAH compounds, contamination sources, human exposures, analytical methods and regulations.